A framework for Strategic planning in Iran's Oil Industry - Salahshouri, Rohollah; Asgharizadeh, Ezzatollah; Safari, Khosro; Noori, Mozhgan (International Journal of Management Excellence (ISSN: 2292-1648), 2017)
The aim of this study is present a framework for strategic planning. On this basis, the oil industry was selected as the spatial domain. In this study, in order to implement the strategic planning, since IT is an inevitable part of today's businesses, we focused on aligning business strategic planning in the oil industry and strategic IT planning. First, to analyze the data, strengths and weaknesses, opportunities and threats in the oil industry were analyzed using the SWOT model. Then, appropriate strategies in the oil industry were identified by using the combination of the Balanced Scorecard method and strategic alignment model, according to the SWOT matrix and causal relationships were drawn and finally, the strategies were rated using TOPSIS technique in order to improve resource allocation and reduce the complexity of decision-making for managers.